Integration of heterogeneous relational databases: RDF mapping approach - Ismail, M.A.; Yaacob, M.; Kareem, S.A. (2008)
Mapping process is important in integrating data and knowledge from multiple heterogeneous relational databases. Mapping from a relational database to a description that uses the Resource Description Framework (RDF) shows promising results where it will not jeopardize the semantics of the data. The integration is also important in realizing simultaneous data query from multiple databases. Thus, this paper defined a practical approach for creating mappings between three relational databases of scholarly content (journal and proceeding) to RDF.